Quantifying the benefits of dynamic line ratings in congestion management for improved wind integration in smart grids - Banerjee, Binayak (Curtin University, 2015)
Grid integration of large scale renewable energy is one of the biggest challenges facing the electricity industry. Network congestion due to insufficient capacity has been identified as one of the key impediments to renewable integration. This thesis proposes novel techniques for incorporating dynamic transmission line ratings which involve temporarily relaxing line thermal constraints to release latent network capacity. It hence quantifies the risks and benefits of using dynamic ratings in decision making.